Glutathione Deficiency in Sinorhizobium meliloti Does Not Impair Bacteroid Differentiation But Induces Early Senescence in the Interaction With Medicago truncatula - Li Yang; Sarra El Msehli; Sofiane Benyamina; Annie Lambert; Julie Hopkins; Julie Cazareth; Olivier Pierre; Didier Hérouart; Samira Achi-Smiti; Eric Boncompagni; Pierre Frendo (Frontiers in Plant Science, 2020)
Under nitrogen-limiting conditions, legumes are able to interact symbiotically with bacteria of the Rhizobiaceae family. This interaction gives rise to a new organ, named a root nodule. Root nodules are characterized by an increased glutathione (GSH) and homoglutathione (hGSH) content compared to roots. These low molecular thiols are very important in the biological nitrogen fixation. In order to characterize the modification of nodule activity induced by the microsymbiont glutathione deficiency, physiological, biochemical, and gene expression modifications were analyzed in nodules after the inoculation of Medicago truncatula with the SmgshB mutant of Sinorhizobium meliloti which is deficient in GSH production. The decline in nitrogen fixation efficiency was correlated to the reduction in plant shoot biomass. Flow cytometry analysis showed that SmgshB bacteroids present a higher DNA content than free living bacteria. Live/dead microscopic analysis showed an early bacteroid degradation in SmgshB nodules compared to control nodules which is correlated to a lower bacteroid content at 20 dpi. Finally, the expression of two marker genes involved in nitrogen fixation metabolism, Leghemoglobin and Nodule Cysteine Rich Peptide 001, decreased significantly in mutant nodules at 20 dpi. In contrast, the expression of two marker genes involved in the nodule senescence, Cysteine Protease 6 and Purple Acid Protease, increased significantly in mutant nodules at 10 dpi strengthening the idea that an early senescence process occurs in SmgshB nodules. In conclusion, our results showed that bacterial GSH deficiency does not impair bacterial differentiation but induces an early nodule senescence.